Electrospun nitric oxide releasing bandage with enhanced wound healing. (February 2015) - Lowe, A.; Bills, J.; Verma, R.; Lavery, L.; Davis, K.; Balkus, K.J.
Graphical abstract: Highlights: Acrylonitrile-based nitric oxide-loaded wound dressing releases 79 μmol NO g −1 over 2 weeks. Wound dressing shows in vivo gene responses from released NO. Significant enhanced healing progression is found when bandage applied to wounds with weekly and daily application. Application of daily NO bandages results in improved wound vascularity. Demonstrate a new potential wound therapy. Abstract: Research has shown that nitric oxide (NO) enhances wound healing. The incorporation of NO into polymers for medical materials and surgical devices has potential benefits for many wound healing applications. In this work, acrylonitrile (AN)-based terpolymers were electrospun to form non-woven sheets of bandage or wound dressing type materials. NO is bound to the polymer backbone via the formation of a diazeniumdiolate group. In a 14 day NO release study, the dressings released 79 μmol NO g −1 polymer. The NO-loaded dressings were tested for NO release in vivo, which demonstrate upregulation of NO-inducible genes with dressing application compared to empty dressings. Studies were also conducted to evaluate healing progression in wounds with dressing application performed weekly and daily. In two separate studies, excisional wounds were created on the dorsa of 10 mice. Dressings with NO loaded on the fibers or empty controls were applied to the wounds and measurements of the wound area were taken at each dressing change. The data show significantly enhanced healing progression in the wounds with weekly NO application, which is more dramatic with daily application. Further, the application of daily NO bandages results in improved wound vascularity. These data demonstrate the potential for this novel NO-releasing dressing as a valid wound healing therapy.